Chemical process equipment selection and design - Couper, James R. (Burlington, MA ; Oxford, UK : Butterworth-Heinemann, 2010)
Chemical Process Equipment is a guide to the selection and design of a wide range of chemical process equipment. Emphasis is placed on specific information concerning the process design and performance of equipment. To this end, attention is given to examples of successful applications, and a generous number of line sketches showing the functioning of equipment is included with many graphs and tables giving their actual performance. For coherence, brief reviews of perininent theory, including numerical examples to illustrate the more involved procedures, are provided in key chapters. Professor Walas, drawing up on his many years of experience in industry and academia, provides a wealth of valuable shortcut methods, rules of thumb, and design by analogy applications. References to sources of more accurate design procedures are cited whenever they are available. To illustrate the data essential to process design, a substantial number of equipment rating forms and manufacturers' questionnaires have been collected. Because decisions often must be based on economic grounds, a short chapter on costs of equipment rounds out the book. Serves as a guide for selecting and designing chemical process equipment. Provides numerous examples with many graphs and tables. Includes a chapter on equipment cost to address important economic concerns.
Includes bibliographical references and index.
Keywords: Chemical engineering -- Equipment and supplies; Chemical processes -- Equipment and supplies; Electronic books